Surgery versus endoscopy with digital single-operator cholangioscopy-guided therapy for Mirizzi syndrome: the SEIZE study - Bronswijk, Michiel; Tengan, Joachim; Arcidiacono, Paolo Giorgio; Bruno, Marco J.; Dhar, Jahnvi; Gerges, Christian; Gupta, Vikas; Hollenbach, Marcus; Johnson, Gavin; Lakhtakia, Sundeep; Lammers, Willem J.; Omoshoro-Jones, Jones A. O.; et al. (Endoscopy, 2025)
Background: The management of Mirizzi syndrome has been primarily surgical, but there are no comparisons between surgical and digital single-operator cholangioscopy (dSOC)-guided treatment. The objective of this study was to compare the safety and other outcomes of the two approaches. Methods: A large multicenter international retrospective analysis was conducted comparing dSOC and surgery in patients with type II-IV Mirizzi syndrome between January 2005 and June 2023. Patients with postsurgical anatomy, Mirizzi type I or V, or previous cholecystectomy were excluded. Results: 290 patients were included (dSOC, n = 176; surgery, n = 114). At baseline, patients undergoing dSOC were older P = 0.006) and exhibited more co-morbidities. While technical success was lower with dSOC (89.8 % vs. 96.5 %; P = 0.04), the need for reintervention was comparable after a median follow-up duration of 741.5 days (interquartile range [IQR] 320-1781) vs. 346 days (IQR 67-1220; P = 0.009). Overall adverse events (10.2 % vs. 41.2 %; P < 0.001) and severe adverse events (1.7 % vs. 15.8 %; P < 0.001) occurred less frequently with dSOC, findings that were confirmed with propensity score-matching. A lower need for hepaticojejunostomy (8.2 % vs. 25.4 %; P = 0.006) and lower rate of conversion to open surgery (6.0 % vs. 22.8 %; P = 0.009) were observed in patients undergoing elective cholecystectomy following dSOC compared with the primary surgery group.Conclusions. Our study demonstrates that the use of dSOC for Mirizzi syndrome is effective, showing superior safety despite being used to treat patients with more underlying co-morbidities. dSOC seems valuable in downgrading the extent of subsequent surgery, by potentially reducing the need for hepaticojejunostomy and conversion to open surgery.